2021
DOI: 10.3389/fendo.2021.724333
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cumulative Live Birth Rate Between Aged PCOS Women and Controls in IVF/ICSI Cycles

Abstract: The present study aimed to assess whether women with polycystic ovarian syndrome (PCOS) ≥35 years age undergoing in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycles experienced a higher cumulative live birth rate (CLBR) over a two-year period compared with age- and body mass index (BMI)-matched patients with tubal factor infertility. Through propensity score matching (PSM) approach, the authors retrospectively analyzed the IVF/ICSI outcomes of 263 PCOS patients (35-46 years of age [mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
2
2
0
Order By: Relevance
“…The largest retrospective investigation on PCOS revealed that individuals aged 20–44 had considerably greater mean number of oocytes retrieved, clinical pregnancy and live-birth rates than the control group [ 30 ]. This has also been supported by previous investigations [ 31 , 32 ]. Increased oocytes retrieved paves the way for more highly qualified embryos.…”
Section: Discussionsupporting
confidence: 91%
“…The largest retrospective investigation on PCOS revealed that individuals aged 20–44 had considerably greater mean number of oocytes retrieved, clinical pregnancy and live-birth rates than the control group [ 30 ]. This has also been supported by previous investigations [ 31 , 32 ]. Increased oocytes retrieved paves the way for more highly qualified embryos.…”
Section: Discussionsupporting
confidence: 91%
“… 31 , 32 Numerous studies consistently report that the CLBR among PCOS patients exceeds that of control groups, 33 , 34 even in women aged ≥ 35. 35 , 36 Our findings align with prior research, reinforcing the notion that PCOS patients achieve higher CLBR than their non-PCOS counterparts. Obesity is recognized for its adverse impact on oocyte quantity and quality, as well as reduced endometrial receptivity, 37 , 38 ultimately influencing embryo implantation and clinical pregnancy rates.…”
Section: Discussionsupporting
confidence: 87%
“…However, other studies have shown inconsistent conclusions. A retrospective cohort revealed that PCOS patients aged 35 years or older had a higher cumulative pregnancy rate and live birth rate but a miscarriage rate similar to that of age-and BMI-matched control patients [37]. Another study concluded that PCOS patients who conceived through IVF had a similar clinical miscarriage rate compared with patients without PCOS [38].…”
Section: Discussionmentioning
confidence: 99%